The Effect of Ratio of Noni and Pineapple Juices and Heating Time on Quality of Mix Noni Candy - Melina Sianturi; Rona Joharmi Nainggolan; Linda Masniary Lubis (Universitas Sumatera Utara, 2014)
The research was conducted to determine the effect of ratio of noni and pineapple juices and heating time on the quality of mix noni candy. This research was conducted using completely randomized design with two factors, i.e. : the ratio of noni and pineapple juices (S) (70% : 30%; 60% : 40%; 50% : 50%; 60% : 40%) and heating time (L) (20 minutes, 25 minutes, 30 minutes, 35 minutes). Parameters analyzed were moisture content (%), ash content (%), vitamine C content (mg/100 g ingredient), total acid (%), total soluble solid (o Brix), organoleptic values of color, flavor, taste and texture. The results showed that the effect of ratio of noni and pineapple juices had highly significant effect on moisture content (%), ash content (%), vitamine C content (mg/100 g ingredient), total acid (%), total soluble solid (o Brix), organoleptic values of color, flavor, taste and texture. The heatingtime had highly significant effect on moisture content (%), ash content (%), vitamine C content (mg/100 g ingredient), total acid (%), total soluble solid (o Brix), organoleptic values of color, flavor, taste and texture. Interactions of the two factors had highly significant effect on moisture content, total acid (%), total soluble solid (o Brix), organoleptic values of color, flavor and taste and had significant effect on ash content (%),vitamine C content (mg/100 g ingredient) and organoleptic values of texture. ratio of noni and pineapple juices of (60% : 40%) and time of heating of (30 minutes) resulted in the best and more acceptable quality of mix noni candy. . Key words : Candy, Heating Time, Noni, Pineapple